Mindfulness, mindset, and motivation an intervention program for speech pathology students - Bentulan, Rozelle Francesca K. (College of Education, University of the Philippines Diliman, 2020)
Attrition and delay rates in Speech Pathology (SP) education are concerning yet no local studies exploring non-cognitive factors associated with academic success have been found. Moreover, no evidence-based, culturally-appropriate intervention program aimed at improving SP student wellness and performance exists. This study explored the relationships among mindfulness, growth mindset, academic intrinsic motivation, and academic performance among 89 Speech Pathology undergraduate students in a university in Manila. It likewise investigated the impact of Mind-Prime, a researcher-made combined mindfulness-mindset intervention program, on ten SP clinical interns. Regression analysis revealed that mindfulness, mindset, and motivational levels do not significantly predict grades. However, correlation analysis revealed a significant association among mindfulness, growth mindset, and academic intrinsic motivation levels. Higher mindfulness level was significantly related to better academic performance. No significant relationship was found between grades and growth mindset or motivation levels. Moreover, a comparison of pre-and post-intervention scale scores showed significant increase in mindfulness, growth mindset, and academic intrinsic motivation levels. Thematic analysis of post-intervention FGD transcripts revealed six themes. Specifically, the participants reported improvements in the areas of (1) academic engagement, (2) emotional self-regulation and well being, (3) perspective transformation, (4) life engagement, (5) self regard, and (6) social cognition. These themes appear to be interrelated and interdependent. Lastly, intervention impact seems to have been strengthened by the interaction between mindfulness and growth mindset. This study provides evidence for the viability of combining mindfulness and mindset training when designing support programs for health professions students.